An Analysis of SIS’s Understanding of Ijtihād from an Islamic Thought Perspective - Kamaruddin, Zuraidah; Wan Ali, Wan Zailan Kamaruddin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2012)
Sisters In Islam (SIS) is a Non-Governmental Organisation (NGO). The group’s formation started in 1987 when several women gathered to concentrate on what they claimed as problems relating to the implementation of some new Islamic Family Laws that were enforced in that year. This situation led to the formation of the core of what was to become Sisters In Islam (SIS) in 1989, and in 1993, they were registered as a Non-Governmental Organisation (NGO) under the name of SIS Forum (Malaysia) Berhad. SIS state that they offer alternative solutions for the problems that they claimed are faced by Muslim society. Since the method of problem solving in Islam is significant to ensure the given solution does not contradict with Islam, this article will analyse the method of problem solving through ijtihād as interpreted by SIS from an Islamic thought perspective.